Progress in the research of nanomaterial-based exosome bioanalysis and exosome-based nanomaterials tumor therapy. (July 2021) - Sun, Zhiwei; Yang, Jingjing; Li, Hui; Wang, Chuanxin; Fletcher, Cameron; Li, Juan; Zhan, Yao; Du, Lutao; Wang, Fenglong; Jiang, Yanyan
Abstract: Exosomes and their internal components have been proven to play critical roles in cell–cell interactions and intrinsic cellular regulations, showing promising prospects in both biomedical and clinical fields. Although conventional methods have so far been utilized to great effect, accurate bioanalysis remains a major challenge. In recent years, the fast-paced development of nanomaterials with unique physiochemical properties has led to a boom in the potential bioapplications of such materials. In particular, the application of nanomaterials in exosome bioanalysis provides a great opportunity to overcome the current challenges and limitations of conventional methods. A timely review of the research progress in this field is thus of great significance to the continued development of new methods. This review outlines the properties and potential uses of exosomes, and discusses the conventional methods currently used for their analysis. We then focus on exploring the current state of the art regarding the use of nanomaterials for the isolation, detection and even the subsequent profiling of exosomes. The main methods are based on principles including fluorescence, surface-enhanced Raman spectroscopy, colorimetry, electrochemistry, and surface plasmon resonance. Additionally, research on exosome-based nanomaterials tumor therapy is also promising from a clinical perspective, so the research progress in this branch is also summarized. Finally, we look at ways in which the field might develop in the future.